Who takes the lead? [Dataset] - Tosun, Jale; Heinz-Fischer, Christin; Luo, Rui (Universität, 2023)
Action is needed from all the major emitting economies if we are to achieve global net-zero carbon dioxide emissions. Climate action takes place at various levels of the political system. In this study, we concentrate on cooperation between the major economies on clean energy technologies in the frame of the Clean Energy Ministerial (CEM; initiated in 2010) and Mission Innovation (MI; initiated in 2015). More precisely, building on research on the European Union's (EU) leadership in international climate politics, we concentrate on how the EU Commission and the EU member states have exerted leadership in these two organizations in the period 2013-2022 (for the CEM) and 2017-2022 (for MI), respectively. We use descriptive techniques and cluster analysis to investigate our original dataset. We find that, first, the EU Commission has been more active in MI than in the CEM. Interestingly the EU Commission's leadership in MI even surpasses that of the United States. Second, the EU Commission has been more active than the EU member states in MI but not in the CEM. Third, Germany and the United Kingdom, together with Italy, the Netherlands, and Denmark, stand out as particularly active in terms of (co-)leading workstreams.